Different Perspectives on Early Childhood Education Curriculum: A Comparison of Experts’ Views - Lathipa Hasanah; Athaya Nadine Zahira; Farsya Nabila Putri; Nur Tiara Indah; Evelyna Iffah Dinayah (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2026)
This study aims to explore in depth the diverse perspectives of education experts on the Early Childhood Education (ECE) curriculum through a literature review approach. The analysis focuses on variations in curriculum approaches shaped by the philosophical backgrounds and sociocultural contexts of each figure. This study employed a qualitative method, using documentation techniques as the primary tool for data collection. The findings indicate that each expert contributes differently to the development of the ECE curriculum. Montessori emphasizes children’s freedom within a structured framework; Ashton-Warner prioritizes experience and local culture; Pratt foregrounds constructive play; Kamii and DeVries focus on constructivism-based exploration; Bereiter supports flexible, interest-based learning; while Engelmann proposes a systematic instructional approach. These findings suggest that the ECE curriculum should be designed contextually and comprehensively by considering children’s individual developmental needs. This study recommends integrating theory and practice as a foundation for developing an ECE curriculum that is relevant and adaptable to various educational contexts.